The Use of Satire Language Style in Dakwah Videos and its Implications For the Learning of Indonesian Language at School - Arlinda, Arlinda; Baadilla, Irwan (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to the use of satirical language style in dakwah videos and its implications for the learning of the Indonesian language at school. The research method used is descriptive qualitative with data analysis techniques. The data collection technique used in this study is the note-taking technique, namely observation, note-taking, and documentation. The research data was obtained from videos, preaching, and dialogue on the YouTube channel "Das'ad Latif." First, identify the style of satirical language used in the YouTube channel "Das'ad Latif." Second, noting the style of satirical language used in the YouTube channel “Das’ad Latif.” Third, analyze the results in depth to find accurate results. Fourth, enter the data into the analysis table. The da'wah video for the YouTube channel "Das'ad Latif" contains the use of satirical language styles, namely irony, cynicism, sarcasm, satire, and innuendo. The results of the research are 86 fragments of notes, which are the research subfocus. Irony was found in 14 passages, cynicism found in 24 passages, sarcasm found in 20 passages, satire found in 16 passages, and innuendo in 12 fragments in the period November and December 2022.